Perbandingan Produksi Panen Pupuk Organik dan Anorganik dan Dampaknya bagi Kesehatan Lingkungan - Muhtiara Yaser; Yayan Sanjaya; Yanti Rohmayanti; Win Heri Sarfudin (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
Indonesia is an agricultural country. The majority of the population work as farmers. The use of anorganic fertilizers and pesticides is excellent because the results are instant and easy to use but have a negative impact on the environment. This study aims to compare the production of red hot chili (Capsicum annum L.) with the use of organic fertilizers and anorganic fertilizers using Randomized Block Ddesign (RBD) method. The data obtained was analyzed using statistics with the ANOVA test and Least Significant Difference (LSD) test. The results of statistical tests indicated that there was no significant difference in the use of optimal inorganic fertilizer (25%) with Biosoltamax brand organic fertilizer for red hot chili production. Inorganic fertilizers have an impact on environmental health. anorganic fertilizers produce residues that are harmful to biota and the environment. Inorganic fertilizers are inversely proportional to the use of organic fertilizers which do not leave residues in the environment and do not have a negative impact on environmental health.